Evaluation of the relationship between thyroid hormones and endometriosis: a clinical investigation - Sanei Taheri, Morteza; Boroujeni, Majid Valiyan; Fouladi, Zahra Mahboubi; Ardebili, Shahla Noori; Chegeni, Samaneh; Moharamzad, Yashar; Abniki, Simin; Hasanzadeh, Sara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Endometriosis is a chronic gynecological condition that affects reproductive-aged women. This study evaluated the correlation between thyroid hormone levels and endometriosis severity. Methods: A cross-sectional study was conducted at Shohada Tajrish Hospital and Atieh Hospital from September 2024 to April 2025. Participants diagnosed with endometriosis underwent clinical, ultrasound, and thyroid hormone assessments. Statistical analyses were used to explore correlations between hormone levels and endometriosis severity. Results: Significant associations were found between anti-TPO levels and UBESS stage 2. Pain severity was higher in moderate disease. However, TSH, T3, and Free T4 levels showed no significant correlations with disease stage or pain severity. Adhesion levels were associated with nodule presence and uterosacral ligament thickness. Conclusions: Elevated anti-TPO levels may indicate autoimmune involvement in moderate endometriosis. Structural markers on ultrasound, such as nodule count and USL thickness, may predict disease severity.